The Practice of Reflection Based on Didactical Design Research: An Analysis of the Geometry Transformation Material - Iik Nurhikmayati; Mohamad Gilar Jatisunda; Nunuy Ratnawulan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
This study aims to identify the possibility of learning obstacles in the concept of Geometric Transformation based on the meaning of the Geometric Transformation concept that students have regarding their experience in obtaining the definition of the Geometric Transformation concept. This study uses a qualitative method and Didactical Design Research for methodological framework that contains three stages of analysis: prospective, metapedadidactic, and retrospective. Teachers who will carry out the learning reflection process based on didactical design research were chosen through purposive sampling as research participants. Forty-eight students took the written test, and then six students were selected by purposive sampling to participate in in-depth interviews. Data analysis was carried out descriptively by reducing data, presenting data, and drawing conclusions. The result indicates that the meaning of the concept of Geometry Transformation, according to students, was the mapping of points in a plane to a set of points in the same plane; the existence of inconsistencies and ambiguity of meaning, and the emergence of the findings of other meaning units of Geometric Transformation concepts. The experience of student meaning shows a tendency for students to get a sense from what is taught by teachers and books with more procedurally oriented concept meanings. Based on the purpose and experience of students' definition, there are learning obstacles in the Geometric Transformation concept, including ontogenic obstacles, epistemological obstacles, and didactical obstacles. These learning obstacles can be a valuable consideration for improving and developing learning designs related to the concept of Geometric Transformation.